Clinical effectiveness of a skills training intervention for caregivers in improving patient and caregiver health following in-patient treatment for severe anorexia nervosa: pragmatic randomised controlled trial. Issue 1 (June 2015) - Hibbs, Rebecca; Magill, Nicholas; Goddard, Elizabeth; Rhind, Charlotte; Raenker, Simone; Macdonald, Pamela; Todd, Gill; Arcelus, Jon; Morgan, John; Beecham, Jennifer; Schmidt, Ulrike; Landau, Sabine; et al.
Abstract : Background: Families express a need for information to support people with severe anorexia nervosa. Aims: To examine the impact of the addition of a skills training intervention for caregivers (Experienced Caregivers Helping Others, ECHO) to standard care. Method: Patients over the age of 12 (mean age 26 years, duration 72 months illness) with a primary diagnosis of anorexia nervosa and their caregivers were recruited from 15 in-patient services in the UK. Families were randomised to ECHO (a book, DVDs and five coaching sessions per caregiver) or treatment as usual. Patient ( n =178) and caregiver ( n =268) outcomes were measured at discharge and 6 and 12 months after discharge. Results: Patients with caregivers in the ECHO group had reduced eating disorder psychopathology (EDE-Q) and improved quality of life (WHO-Quol; both effects small) and reduced in-patient bed days (7–12 months post-discharge). Caregivers in the ECHO group had reduced burden (Eating Disorder Symptom Impact Scale, EDSIS), expressed emotion (Family Questionnaire, FQ) and time spent caregiving at 6 months but these effects were diminished at 12 months. Conclusions: Small but sustained improvements in symptoms and bed use are seen in the intervention group. Moreover, caregivers were less burdened and spent less time providing care. Caregivers had most benefit at 6 months suggesting that booster sessions, perhaps jointly with the patients, may be needed to maintain the effect. Sharing skills and information with caregivers may be an effective way to improve outcomes. This randomised controlled trial (RCT) was registered with Current Controlled Trials ISRCTN06149665.